Atraumatic forearm swelling in a patient with poorly controlled asthma. (2021) - Leon, Matthew; Liotta, Robert; Aryal, Shambhu; Vangeertruyden, Peter; Tintle, Scott; Klassen-Fischer, Mary; Holley, Aaron; Kelly, William; Collen, Jacob
Abstract: We present a case of sarcoidosis presenting as unilateral forearm swelling. A 65-year-old male with a long history of asthma presented with unexplained left forearm and hand swelling. Over many years, chest imaging had been devoid of adenopathy or parenchymal findings suspicious for sarcoid, until after the extremity findings emerged. The patient was diagnosed based on subcutaneous, dermal and mediastinal lymph node histopathology. Sarcoid presenting with isolated extremity findings prior to more typical pulmonary manifestations is rare even for cutaneous or soft tissue sarcoid, highlighting the need to maintain a high index of suspicion for sarcoidosis.